The Correlation between Vocabulary Achievement and Reading Comprehension - Arni Fitri; Abdul Aziz Rifaat (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
The study investigated the correlation between students’ vocabulary mastery and their reading comprehension. Data were collected from 32 eighth grade students of SMPN 11 Palembang. The test item of vocabulary mastery and reading comprehension were given to the students to measure their level of vocabulary mastery and reading comprehension. The results were compared to find out the correlation between those variables. The result showed that there was a significant correlation between students’ vocabulary mastery and their reading comprehension. The technique of collecting data was by using a test. A try out test was also done to find out the validity. After the data of the students’ vocabulary mastery and their achievement in reading comprehension were collected, the data werestatistically computed to find out the correlation between the two variables. The result of applying the pearson correlation shows that the coefficient correlation is 0. 807. It means that there is a significant correlation between the vocabulary mastery and reading comprehension. It is suggested that to have a good mastery of reading comprehension, students should have a good mastery of vocabulary.